Association of maternal nutritional status with neonatal anthropometry: a cross-sectional study - Saeed, Ayesha; Samra Imran; Ayesha Humayun (Journal of the Pakistan Medical Association, 2022)
Objective: To identify the association of maternal nutritional status with neonatal anthropometry. Method: The multi-centre, cross-sectional survey was conducted at two government and 5 private hospitals in Lahore, Pakistan, from July 2016 to August 2017, and comprised mothers and their neonates. A semi-structured self-administered questionnaire was used along with data from patient files. Maternal nutritional status was assessed through biochemical profile. Standard procedures and safety measures were employed during data collection of neonatal anthropometric measurements. Data was analysed using SPSS 22. Results: Of the 800 subjects, 407(50.9%) were from government hospitals and 393(49.1%) from private hospitals. The mean maternal age was 27.72+14.42 years. Among the neonates, 365(45.6%) were girls and 435(54.4%) were boys. Significantly lower anthropometric measurements were noted in mothers with poor haemoglobin, haematocrit, red blood cell, fasting glucose levels as well as those with higher uric acid, and lower serum albumin, total protein, and in those with blood in urine (p<0.05). Conclusion: Maternal biochemical markers were found to be critical in evaluating mothers at risk of delivering neonates with low anthropometric measurements. Key Words: Maternal health, Nutrition assessment, Anthropometry, Blood cell count.